Pengaruh Green Marketing dan Brand Image Terhadap Keputusan Pembelian Tupperware di Jalan Setia Budi - Tita Kiftiah; Eka Dewi Setia Tarigan; Safrida Hafni Sahir; Dahrul Siregar (Universitas Medan Area, 2022)
The purpose of this study was to determine the effect of green marketing on purchasing decisions, to determine the effect of brand image on purchasing decisions and to determine the effect of green marketing and brand image on purchasing decisions of Tupperware on Jalan Setia Budi. The population in this study were the surrounding communities who purchased Tuppaware products for 2020 on Jalan Setia Budi Lingkungan I as many as 1718 people, where the sample was 94 people who were carried out with the Slovin formula. The data collection technique used in this study was carried out by distributing questionnaires. The analysis technique used in this research is multiple linear regression, partial test (t test), simultaneous significance test (F test) and the coefficient of determination. The results show that partially Green Marketing has a positive and significant effect on Tupperware Purchase Decisions, Brand Image has a positive and significant effect on Tupperware Purchasing Decisions and Simultaneously Green Marketing and Brand Image have a significant effect on Tupperware Purchasing Decisions on Jalan Setia Budi.